2011
DOI: 10.1002/lary.22362
|View full text |Cite
|
Sign up to set email alerts
|

Hearing results and quality of life after streptomycin/dexamethasone perfusion for meniere's disease

Abstract: Streptomycin/dexamethasone inner ear perfusion is as safe to the hearing of patients with Meniere's disease as other aminoglycoside regimens and provides a significant improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Shea et al [19] used IT low-dose streptomycin/ high-dose dexamethasone mixture plus intravenous dexamethasone combination for 3 days in Meniere's disease patients, and found the vertigo control rate as 88%, and hearing loss rate as 15.7%. It has been known that corticosteroids pass into the inner ear and attach to their own receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Shea et al [19] used IT low-dose streptomycin/ high-dose dexamethasone mixture plus intravenous dexamethasone combination for 3 days in Meniere's disease patients, and found the vertigo control rate as 88%, and hearing loss rate as 15.7%. It has been known that corticosteroids pass into the inner ear and attach to their own receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoglycoside (AG) antibiotics such as gentamicin, neomycin, amikacin, kanamycin, tobramycin, and others are useful agents in the treatment of both serious bacterial nfections (1) and Ménière's disease (2,3). These antimicrobials are commonly used worldwide because they are less expensive than other antibiotics, and in some countries, they are less regulated by prescription-only sale.…”
mentioning
confidence: 99%
“…The authors used the MD Outcome Questionnaire survey to analyze treatment outcomes. Although they reported that 88% of the patients had improvements in their "vertigo subscore", a considerable amount of hearing loss (17.9%) occurred in these patients [20] . We think that an ideal combination therapy should incorporate the beneficial effects of both agents while minimizing their side effects.…”
Section: Discussionmentioning
confidence: 95%